Tradisi Wela-Wela Dalam Perkawinan Di Desa Air Nanang Kecamatan Siritaun Wida Timur Kabupaten Seram Bagian Timur - Rumbara, Vifi L.; Kubangun, Nur Aida; Pusparani, Rina (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
The Wela-wela tradition is a deeply rooted cultural practice that plays a significant role in the wedding ceremonies of certain Indonesian communities. This tradition is rich in symbolism and is carried out in three distinct phases, each holding its own cultural significance. The process begins with a deliberation or consultation among the families involved, highlighting the communal aspect of the tradition. The first phase of the Wela-wela occurs when the groom arrives at the bride's house, specifically in front of the sabuah (a ceremonial tent), marking the initial formal meeting between the two families. This moment is crucial as it symbolizes the groom's respectful approach and request for the bride's hand in marriage. The second phase takes place at the front door of the bride's house, where the groom is met with another Wela-wela, representing a more intimate acceptance by the bride's family. This step underscores the importance of familial consent and the gradual transition of the bride from her family to the groom. The final Wela-wela occurs when the groom comes to escort the bride to their new home, symbolizing the completion of the union. This tradition not only serves to honor the bride and her family but also adds a festive and respectful atmosphere to the wedding ceremony. Through these rituals, the Wela-wela tradition reinforces the values of respect, family unity, and cultural heritage, making it a vital component of the wedding process.